Technology Acceptance for an Intelligent Comprehensive Interactive Care (ICIC) System for Care of the Elderly: A Survey-Questionnaire Study - Wong, Alice M. K.; Chang, Wei-Han; Ke, Pei-Chih; Huang, Chun-Kai; Tsai, Tsai-Hsuan; Chang, Hsien-Tsung; Shieh, Wann-Yun; Chan, Hsiao-Lung; Chen, Chih-Kuang; Pei, Yu-Cheng (PloS one, 2012)
The key components of caring for the elderly are diet, living, transportation, education, and safety issues, and telemedical systems can offer great assistance. Through the integration of personal to community information technology platforms, we have developed a new Intelligent Comprehensive Interactive Care (ICIC) system to provide comprehensive services for elderly care. The ICIC system consists of six items, including medical care (physiological measuring system, Medication Reminder, and Dr. Ubiquitous), diet, living, transportation, education (Intelligent Watch), entertainment (Sharetouch), and safety (Fall Detection). In this study, we specifically evaluated the users' intention of using the Medication Reminder, Dr. Ubiquitous, Sharetouch, and Intelligent Watch using a modified technological acceptance model (TAM). A total of 121 elderly subjects (48 males and 73 females) were recruited. The modified TAM questionnaires were collected after they had used these products. For most of the ICIC units, the elderly subjects revealed great willingness and/or satisfaction in using this system. The elderly users of the Intelligent Watch showed the greatest willingness and satisfaction, while the elderly users of Dr. Ubiquitous revealed fair willingness in the dimension of perceived ease of use. The old-old age group revealed greater satisfaction in the dimension of result demonstrability for the users of the Medication Reminder as compared to the young-old and oldest-old age groups. The women revealed greater satisfaction in the dimension of perceived ease of use for the users of Dr. Ubiquitous as compared to the men. There were no statistically significant differences in terms of gender, age, and education level in the other dimensions. The modified TAM showed its effectiveness in evaluating the acceptance and characteristics of technologic products for the elderly user. The ICIC system offers a user-friendly solution in telemedical care and improves the quality of care for the elderly.